DYNAMICS OF DOMESTIC WORKS IN INDIA: AN ANALYTICAL VIEW ON WOMEN’S CONTRIBUTION - Lilee, Mayanglambam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The dynamics of domestic work are multifaceted and debates on women’s undervalued domestic works in the last six decades remain inconclusive at policy level as majority of Indian women are still engaging in the unorganized sectors. According to the International Labour Organization (ILO), over 4.75 million people in India are employed as domestic workers, of which over 80 per cent are women. Even if women’s contribution is acknowledged in some aspects, they are still largely excluded from formal economic analysis globally. In this backdrop, this paper attempted to review the relevant literature critically and explores the dynamics of women’s paid and unpaid work in domestic services by comparing their critical role in maintaining households and contributing to the economy. Further, the paper discusses the live experiences of Manipuri women’s contribution in domestic services. The findings underscore the necessity of recognizing and valuing domestic labour to promote gender equity and social justice.